2018
DOI: 10.1016/j.ijid.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of Enterococcus faecalis bacteremia with dalbavancin as an outpatient in an intravenous drug user

Abstract: This report describes the treatment of a 35-year-old male who presented to the emergency department with an empyema, and who had a long hospital course complicated by a catheter-related bloodstream infection and a history of intravenous drug use. Blood culture results confirmed Enterococcus faecalis. He was not a candidate for outpatient intravenous therapy and needed 14days of treatment, but was able to be discharged with a 3-day supply of oral levofloxacin to complete treatment for his empyema and 1 dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Recent anecdotal reports of the efficacy of dalbavancin in bloodstream infections have been published [14][15][16][17][18][19][20][21][22][23][24][25][26]. A retrospective cohort study conducted in the University Hospital of Vienna between January 2015 and December 2016 showed that microbiological and clinical success was achieved in 93% (25/27) of patients who received dalbavancin either as primary or sequential treatment for infective endocarditis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent anecdotal reports of the efficacy of dalbavancin in bloodstream infections have been published [14][15][16][17][18][19][20][21][22][23][24][25][26]. A retrospective cohort study conducted in the University Hospital of Vienna between January 2015 and December 2016 showed that microbiological and clinical success was achieved in 93% (25/27) of patients who received dalbavancin either as primary or sequential treatment for infective endocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Four case reports described successful treatment with dalbavancin [ 16 , 19 , 21 , 23 ]: the first described successful treatment of catheter-associated bloodstream infection due to E. faecalis in an intravenous drug user [ 19 ], the second showed successful treatment of a 54-year-old man with MSSA bacteremia secondary to septic phlebitis [ 21 ], the third showed successful treatment of a 27-year-old woman with MRSA tricuspid-valve endocarditis with septic pulmonary emboli [ 16 ], and the fourth showed successful treatment of an 88-year-old woman with MRSA prosthetic vascular graft infection [ 23 ]. A phase 2b multicenter randomized clinical trial (NCT04775953) that is currently enrolling patients will compare the safety and efficacy of dalbavancin with standard-of-care antibiotics for the completion of therapy of complicated S. aureus bacteremia or right-sided native valve infective endocarditis in patients who have cleared their bacteremia [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“… 5 Streptococcus spp. 4 P. acnes 21 Others 90 days after the last dose of dalbavancin Overall clinical success: 89% (66.7% CR-BSI) 90-day mortality rate: 5% (33.3% CR-BSI) Overall clinical failure: 5% NA 3% (overall) Nunez-Nunez et al, 2018 40 Prospective observational 1 (19 overall patients included in the study) 1 Long-term suppressive therapy in prosthetic graft infection 100% Dalbavancin 750 mg (LD) + 375 mg weekly for a total of 62 doses (IHD) 1 E. faecium 90 days Clinical success: 100.0% Relapse: 0.0% None Hitzenbichler et al, 2020 46 Case series 4 4 Long-term suppressive therapy for BSI due to intravascular source 2 LVAD 1 Transfemoral aortic valve implantation 1 Prosthetic aortic valve 100% Dalbavancin 1000 mg (LD) + 375/500 mg/weekly or 1500 mg (LD) + 1000 mg biweekly 2 E. faecalis 1 E. faecium + CoNS 1 MSRA NA Overall clinical success: 50% Overall mortality rate: 75% Relapse: 25% 50% ( C. difficile infection – Rash) Jones et al, 2018 47 Case report 1 CR-BSI with associated empyema OPAT Vancomycin + Piperacillin-Tazobactam + Levofloxacin Dalbavancin 1500 mg single dose E. faecalis NA Clinical success: 100.0% Relapse: 0.0% None Cho et al, 2015 48 Case report …”
Section: Real-world Use Of Dalbavancin For Off-label Indicationsmentioning
confidence: 99%
“…Ten observational studies, one case series, and six case reports 31,[33][34][35][36][37][38][39][40][41][46][47][48][49][50][51][52] assessed the efficacy and safety of dalbavancin for the treatment of bloodstream infections (BSIs) and vascular infections (Table 3). Overall, 144 patients affected by BSIs or vascular infections were treated with dalbavancin, resulting in a clinical success of 81.3%.…”
Section: Bloodstream and Vascular Infectionsmentioning
confidence: 99%
“…Small clinical trials have demonstrated efficacy of dalbavancin in catheter-related bloodstream infections (Raad et al, 2005) and osteomyelitis (Rappo et al, 2019b), and case reports have demonstrated successful use of dalbavancin in treating MRSA pneumonia (Barber et al, 2017), bacteremia (Jones et al, 2018) and endocarditis (Table 1). In most case reports of gram-positive bacteremia with infective endocarditis, dalbavancin was used only after clearance of bacteria from the bloodstream with conventional…”
Section: Introductionmentioning
confidence: 99%